In‐hospital development of an aorto‐cardiac fistula in a Warmblood gelding with chronic renal disease. (23rd August 2019) - Baker, R. E.; Schlipf, J. W.; Scollan, K. F.; LeBlanc, N. L.; Russell, D. S.
Summary: A 20‐year‐old Warmblood gelding presented for evaluation and treatment of ventral oedema and azotaemia of unknown aetiology. On presentation, a diastolic heart murmur was appreciated and echocardiography revealed moderate aortic insufficiency due to chronic degenerative valve disease. The horse was hospitalised and failed to respond to oral and i.v. fluids and diuretics. Following discontinuation of all fluid and diuretic therapy, the horse became acutely agitated and developed monomorphic ventricular tachycardia. The ventricular tachycardia spontaneously converted to normal sinus rhythm, however the heart murmur changed in timing to a right basilar continuous murmur and bounding jugular pulses were noted. Repeat echocardiogram revealed an aorto‐cardiac fistula with dissection into the basilar interventricular septum and left‐sided chamber volume overload that was not previously present. Attempts at stabilisation were unsuccessful and euthanasia was elected. Post‐mortem examination confirmed chronic renal disease of unknown aetiology in addition to an aorto‐cardiac fistula originating from the right sinus of Valsalva with subsequent dissection into the basilar interventricular septum.